2023
DOI: 10.2176/jns-nmc.2022-0336
|View full text |Cite
|
Sign up to set email alerts
|

Relief of Central Poststroke Pain Affecting Both the Arm and Leg on One Side by Double-independent Dual-lead Spinal Cord Stimulation Using Fast-acting Subperception Therapy Stimulation: A Case Report

Abstract: Central poststroke pain is a chronic, intractable, central neuropathic pain. Spinal cord stimulation is a neuromodulation therapy for chronic neuropathic pain. The conventional stimulation method induces a sense of paresthesia. Fast-acting subperception therapy is one of the latest new stimulation methods without paresthesia. A case of achieving pain relief of central poststroke pain affecting both the arm and leg on one side by double-independent dual-lead spinal cord stimulation using fast-acting subpercepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…It has been suggested that SCS with the latest stimulation patterns has higher pain relief effects than the conventional tonic stimulation [ 15 17 ]. Furthermore, the latest new stimulation patterns may be effective in cases where the conventional tonic stimulation cannot be continued because of the discomfort of the paresthesia [ 18 20 ]. Meanwhile, which stimulation is most effective for which kind of neuropathic pain remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that SCS with the latest stimulation patterns has higher pain relief effects than the conventional tonic stimulation [ 15 17 ]. Furthermore, the latest new stimulation patterns may be effective in cases where the conventional tonic stimulation cannot be continued because of the discomfort of the paresthesia [ 18 20 ]. Meanwhile, which stimulation is most effective for which kind of neuropathic pain remains unclear.…”
Section: Introductionmentioning
confidence: 99%